Production of hydrogen by Enterobacter aerogenes in an immobilized cell reactor - Satar, I. (Elsevier Ltd, 2017)
The production of hydrogen from glucose by using Enterobacter aerogenes ATCC 13048 (E. aerogenes) in an immobilized cell reactor (ICR) was investigated. The effect of several factors, such as the glucose concentration, feed flow rate, and fermentation time were examined. The highest amount of hydrogen (9.44 mmol H2/g glucose) was obtained at a glucose concentration of 8 g/L, flow rate of 0.5 mL/min, retention time of 24 h and at a temperature of 30 °C. Meanwhile, the highest amount of carbon dioxide (1.68 mmol CO2/g glucose) was obtained at a glucose concentration of 10 g/L, flow rate of 0.7 mL/min, hydraulic retention time of 24 h and at a temperature of 30 °C. The hydrogen and carbon dioxide production were affected by glucose concentration, hydraulic retention time (HRT) and fermentation time. This study showed that the ICR was a very efficient method for the production of hydrogen and carbon dioxide gases. © 2016 Hydrogen Energy Publications LLC